The Little Data Book on Private Sector Development 2009 - World Bank (World Bank, 2012)
The little data book on private sector development coincides with the unfolding of the global financial crisis. There is strong evidence that crises can stimulate reform of the investment climate. A better investment climate makes economic adjustment easier and helps attract capital to create jobs and provide basic services. Well functioning finance markets and a robust private sector are critical in increasing productivity and growth and in spreading equality of opportunity. The availability of cross-country data on the business environment has expanded rapidly in recent years, including data from the World Bank's doing business project and enterprise surveys. These data show the scope and types of regulations that enhance and constrain business activity while providing information on business owners' assessments of the business environment. Included in this guide are indicators on the economic and social context, the business environment, private sector investment, finance and banking, and infrastructure. Though a pocket guide cannot include all relevant variables, the indicators that are included provide users with a general understanding of the private sector in each country. Indicators displayed in the tables are defined in the glossary, which also lists data sources.